Introduction to design and analysis with advanced composite materials - Swanson, Stephen R (Prentice Hall, 1997)
Focusing on fundamentals while presenting more advanced topics, this introductory text, by presenting basic analytic and design principles, offers the knowledge required to effectively design structures, using advanced composite materials. It examines material forms, properties and manufacturing techniques.